Proof of Einstein’s postulates - Golovkin, BG (Annals of Mathematics and Physics, 2022)
Based on the assumption that the experiment confirms the STR, it is shown that the value of the speed of light is a very slowly decreasing function of its frequency, so that at a frequency of 2.2989.10-18 S-1, the speed of light becomes zero. Such light represents resting particles – photonics that could serve as the Absolute Reference System, but due to their negligible mass, do not have a noticeable effect on the processes taking place. This explains Einstein’s principle of relativity. The formulas for the change in the speed and frequency of light during the transition from one IRS to another, within the measurement error, remain unchanged, which proves the postulate of the constancy of the speed of light in any IRS. It is shown that all STR formulas include not the speed of light, but the fundamental constant C, equal to the speed of light with a frequency ν = ∞. The proposed explanation of the correctness of Einstein’s postulates is logically, apparently, the only possible one.